Occupational Safety And Health Risk For Bee Farmers In The Sari Nektar Tumpang Community - Bayu Satriyo Aji; Ani Asriani Basri; Fariz Zuvil Arganata; Nafilatul Fitri (Universitas Muhammadiyah Malang, 2025)
The results of observations of Occupational Safety and Health in the Tumpang Sari Nektar Association's beekeeping farmers have identified 27 potential hazards in the Sari Nektar Association's beekeeping farms, which have the phenomenon of work accidents, namely farmers being pricked by nails when lifting bee boxes. The aim of this research is to analyze the potential occupational safety and health hazards that exist in pollen nectar bee farms, analyze the assessment of occupational safety and health hazards that exist in pollen nectar bee farms, analyze risk assessment controls consisting of opportunities and consequences that become disturbance phenomena in nectar beekeeping. The research method used is semi-qualitative numerical with data processing techniques using IBPR. Based on analysis using the IBPR risk assessment method. The output of hazards in beekeeping has been identified as 27 potential hazards in beekeeping. and risk assessment on livestock has identified that the highest risk lies in the risk of bee pollen harvesting activities, as well as providing PPE control and controlling the consequences. The conclusion is that there is a potential danger in beekeeping, it has been identified that Paguyuban Sari Nektar Tumpang's beekeeping is a high-risk job. In accordance with the hierarchy of control, these hazards must be controlled with the aim of minimizing the risks and dangers of work accidents for bee farmers.